Ikonografi og performance – et umage eller komplementært par? - Kaspersen, Søren (Hikuin, 2017)
Iconography and performance – a mismatched or complementary couple? By Søren Kaspersen The article discusses how iconography and performance can support each other as analytical tools and also be prerequisites of each other, related to different subject matters as historia, the Romanesque fauna and late Gothic ornament as dense foliage as well as to the other articles of the publication. Panofsky’s method is compared with Aby Warburg’s different and more performative approach, and a plaidoyer is made for a historical anthropology or a psyche history as a goal for the investigations, guided or framed by Norbert Elias’ idea of a close connection between sociogenese and psychgenese. The main conclusion is that iconography/iconology is very valuable for the uncovering of narrative and symbolic meaning in the pictorial arts while the performative analysis expose the function of these meanings for the educational and civilizing processes in formation of the mental architecture or human psyche.